Bycatch of franciscana dolphins Pontoporia blainvillei and the dynamic of artisanal fisheries in the species' southernmost area of distribution - María Fernanda Negri; Pablo Denuncio; María Victoria Panebianco; Humberto Luis Cappozzo (Brazilian Journal of Oceanography, 2012)
In Argentina, the franciscana dolphin is one of the most vulnerable cetaceans regularly entangled in coastal artisanal fishery nets. The aim of this paper is to estimate the species' incidental mortality on the Southern coast of Buenos Aires province through interviews with the captains of artisanal fishing vessels, in the period 2006-2009. Franciscana bycatch was reported for gillnets and shrimper gear all year round but it occurred more frequently between October and February, at 5 km offshore and 10-20 m depth. The estimated mean annual incidental mortality was 107 dolphins (CI 95% = 87-129), 92 caught in gillnets (CI 95% = 73-112) and 15 in shrimpers' gear (CI 95% = 8-25) with a capture per unit effort of 0.029 dolphins per km of gillnet (CI 95% = 0.023-0.036) and 0.022 per shrimpe r's net (CI 95% = 0.012-0.035). Annual fluctuations were due to differences in the number of gillnetting fishing days. If mortality estimates for the Northern coast are also taken into account, values attain a maximum of 360-539 dolphins bycaught in the entire Buenos Aires province, representing 2.5-3.7% of the species' abundance in Argentina. This will inevitably lead to the decline of franciscana dolphin populations in the near future unless alternative fishing grounds are identified and alternative gearadopted. Na Argentina, a toninha é um dos cetáceos mais vulneráveis devido às capturas por rede de pesca artesanal. O presente estudo teve como objetivo estimar as capturas acidentais no sul da província de Buenos Aires, através de entrevistas aos capitães de barcos de pesca artesanal, entre os anos 2006-2009. As capturas foram reportadas para redes de emalhe e de camarão; com as mais altas frequências entre outubro e fevereiro, a 5 km da costa e 10-20 m de profundidade. A mortalidade acidental média anual estimada foi de 107 golfinhos (IC 95% = 87-129), 92 em redes de emalhe (IC 95% = 73-112) e 15 em redes de camarão (IC 95% = 8-25), com uma captura de 0,029 golfinhos/km de rede de emalhe (IC 95% = 0,023-0,036) e 0,024/rede de camarão (IC 95% = 0,012-0,035). As flutuações anuais responderam principalmente às diferenças nos dias de pesca. Considerando o último levantamento estimativo feito para o norte costeiro da província, estima-se uma mortalidade entre 360-539 golfinhos/ano em toda a província de Buenos Aires. Esses valores correspondem de 2,5-3,7% da abundância populacional da Argentina; o que traria como consequência um declínio populacional da espécie, tornando-se fundamental encontrar alternativas de pesca para a área.